Tetanus as a cause of acute renal failure: possible role of rhabdomyolysis - Martinelli,Reinaldo (1993)
To study the frequency and examine the role of rhabdomyolysis in the acute renalfailure in tetanus 18 patients with the diagnosis of generalized tetanus consecutively admitted to the infectious disease hospital were evaluated. Ofthese 14 were male and 4female with mean age of 31.8± 2.0 years. Except for mild proteinuria recorded in 9 patients, the urinalysis were unremarkable. Serum creatinine higher than 1.4mg/dl was recorded in 39% of the patients, abnormal levels of CPK in 87,5% and serum myoglobin greater than 120µg/l in 39% of the patients. Oliguria was documented in one patient and none required diafysis therapy. No correlation wasfound between renal failure and myoglobin and/or CPK serum levels. Acute renalfailure in tetanus was not infrequent; usualfy it was non-oliguric, mild and transient and not related to the severity of the disease or to serum levels of myoglobin and/or CPK.